PERAN AKTIF MAHASISWA DAN MASYARAKAT DALAM MENGHADAPI FENOMENA PANDEMI COVID-19 DI DESA TUWUNG KECAMATAN KAHAYAN TENGAH - Rinto Alexandro; Suita Manurung; Puteri Neriasi; Oliver Situmorang; Ahmad Hidayat; Tantan Gunawan; Astri Susana; Regina Halent; Nurul Hazmi; Seri Wahyuni; Dechrist Event; Zakia Aprilianti; Supri Supri; Anre Tampubolon; Nia Damatik; Gari Purwanto; Hernawati Hernawati (Bakti Banua : Jurnal Pengabdian Kepada Masyarakat, 2021)
In 2020, mankind throughout the world will be shaken by the Corona Virus (Covid-19) pandemic which has greatly affected people's lives and caused a lot of panic. Hundreds or even thousands of humans have been infected and many have died due to the Covid-19 Virus. Because the Corona Virus (Covid-19) also makes the people of Tuwung village, Kahayan Tengah district, Pulang Pisau Regency, they are limited in carrying out daily routines such as worship, school, teaching, even hobby activities such as playing volleyball and others. Another problem that occurs is that some of the people of Tuwung village also lack discipline in carrying out health protocols such as crowding in many people, not wearing protective masks, still shaking hands, and others. In this case, Palangka Raya University students do not remain silent, starting from providing many appeals, education and assistance to the community in overcoming the Covid-19 outbreak, the people of Tuwung village are maintained and safe through the KKN-T Period II activities of Palangka Raya University. The Indonesian government implements a home system where Indonesians are required to be quiet and work in their own homes. And with this rule, the KKN-T Period II Students of Palangka Raya University carry out activities that apply the Work from Home system and still follow the applicable health protocols. The purpose of this activity is to provide an example and understanding for the Tuwung village community in order to comply with the applicable regulations in the country of Indonesia. So that through this activity it can help the government and medical personnel to break the chain of spreading the Corona Virus (Covid-19) in Indonesia. And with this activity it will also make the public more aware of the importance of implementing health protocols both in the red zone and in the green zone.